2008
DOI: 10.1590/s0074-02762008000500014
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis strains of the Beijing genotype are rarely observed in tuberculosis patients in South America

Abstract: The frequency of the Beijing genotype of Mycobacterium tuberculosis as a cause of tuberculosis (TB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
43
3
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 14 publications
14
43
3
6
Order By: Relevance
“…Previous studies analysing Mtb isolates from the state of Rio Grande do Sul in Southern Brazil reported the prevalence of LAM, unknown, H e T, as described in our study; however, the authors analysed a lower number of isolates within a region of low TB prevalence (Noguti et al 2010, Von Groll et al 2010. Interestingly, no Beijing and CAS strains were found in the investigation herein, an observation that is corroborated by a recent report from Ritacco et al 2008. A global perspective on the spoligotype binary patterns, related SITs, and genotypic lineages is illustrated in the Phylogenetic tree shown in Figure. The majority of LAM and T strains in our study originated in patients from Belo Horizonte.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies analysing Mtb isolates from the state of Rio Grande do Sul in Southern Brazil reported the prevalence of LAM, unknown, H e T, as described in our study; however, the authors analysed a lower number of isolates within a region of low TB prevalence (Noguti et al 2010, Von Groll et al 2010. Interestingly, no Beijing and CAS strains were found in the investigation herein, an observation that is corroborated by a recent report from Ritacco et al 2008. A global perspective on the spoligotype binary patterns, related SITs, and genotypic lineages is illustrated in the Phylogenetic tree shown in Figure. The majority of LAM and T strains in our study originated in patients from Belo Horizonte.…”
Section: Resultssupporting
confidence: 91%
“…Unfortunately, these features are not easily found in all settings, and convenience samples are thus used for these purposes. The Beijing lineage was absent in isolates from Chile, Ecuador and Colombia in a study conducted in several Latin American countries from 1997 to 2003 (8). However, it might have remained undetected due to limitations in the study's sample representativeness.…”
Section: Discussionmentioning
confidence: 93%
“…One of the few multinational studies in this region revealed a heterogeneous distribution of the Beijing lineage in the seven countries surveyed (8). In the four countries where it was detected, its prevalence varied widely: Perú (5.9%), Argentina (1.0%), Brazil (0.8%) and Paraguay (0.6%).…”
mentioning
confidence: 99%
“…En los Estados Unidos de América, específicamente en Nueva York, en el año 1991, durante un brote que afectó a ocho pacientes www.sochinf.cl con TBC resistente a isoniacida, rifampicina, etambutol, estreptomicina, kanamicina, etionamida y rifabutina, se identificó el genotipo "W", que fue posteriormente asociado a otros cinco brotes en hospitales del área de Nueva York. Este genotipo se relacionó estrechamente con el genotipo Beijing (Beijing W) 12,13 . En América Latina, a pesar del bajo reporte de genotipo Beijing, éste ha sido detectado en forma significativa en cepas peruanas, tanto susceptibles como resistentes, lo cual podría explicarse por la migración asiática 6,8 .…”
Section: Introductionunclassified
“…En el año 2008 y posteriormente en el año 2012, Ritacco y cols., en Buenos Aires, Argentina, estudiaron cepas de América Latina, incluyendo 35 y 13 cepas de Chile, respectivamente. Estos estudios no caracterizaron la totalidad de los cepas y sólo se describe el genotipo LAM en una cepa, sin encontrar el genotipo Beijing 5,13 .…”
Section: Introductionunclassified